An empirical study about catering theory of dividends: The proof from Chinese stock market - Xiaoguang Lu; Yiran Xi; Diqian Lu (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: This paper aims to study the remarkable effect of dividends catering in Chinese stock market, and its significance on dividend policy and investment decisions. Is there a significant difference in operation status of companies between issuing cash dividend and those without cash dividend, and which one is the better? Is there a significant difference in income level of stocks between issuing cash dividend and those without cash dividend, which one is the higher? Is the irrational preference of cash dividend detracting along with the development and improvement of securities market? All issues above need the market inspection. Design/methodology/approach: Based on related dividend theories and the empirical data of Chinese securities market, we construct three portfolios including stock dividend, cash dividend and non-dividend. The paper studies the returns from these three kinds of portfolios which is analyzed by the least significant difference method, co-integration model, Sharpe index model, and error correction model, and then finally comes to the conclusions. Findings: The main finding is that there is significant effect of dividends catering in Chinese stock market; the income level of cash dividend portfolio is significantly lower than that of other portfolios; the listed companies issuing stock dividend have a high investment value. Originality/value: Through collecting a lot of data from the year 2004 to 2009 and developing models to analyze, the paper deem that whether the earnings growth or not determines the dividend policy of listed companies, and that stock dividend is the natural choice for those listed companies which have sustainable development advantages.
Keywords: 650; dividend policy; catering theory of dividends; stock dividend; sharpe index model; co-integration; error correction model; significant difference method